STRATEGI PEMBINAAN PESERTA DIDIK DALAM RANGKA PENGUATAN PENDIDIKAN KARAKTER BERBASIS NILAI PANCASILA DI SEKOLAH DASAR - Maisyaroh Maisyaroh; Sri Untari; Tutut Chusniyah; Dedi Prestiadi; Endrik Mas Yulaidi; Maulana Amirul Adha; Bagus Rachmad Saputra; Nova Syafira Ariyanti (Universitas Negeri Malang, 2021)
Abstract: The purpose of this study is to describe the strategy of strengthening character education based on Pancasila values through coaching students at the Elementary School Laboratory Universitas Negeri Malang, Blitar City. The research was conducted qualitatively with a case study approach. Data obtained through unstructured interviews, observation and documentation study. Data credibility checks were carried out using triangulation techniques, random member checks and discussion with fellow researchers. The results of this study indicate that the strategy of coaching students in order to strengthen Pancasila value-based character education is divided into learning and non-learning aspects. The strategy to strengthen character education based on Pancasila values in schools is implemented in accordance with the vision and mission of the school including being adjusted to the characteristics of school learning oriented towards western education patterns by focusing on understanding and using English as the excellence of the school. Combined with eastern customs which are described in the character building activities of students.Keywords: strategy; strengthening character education; pancasila value; elementary school laboratory.Abstrak: Tujuan penelitian ini yakni mendeskripsikan strategi penguatan pendidikan karakter berbasis nilai pancasila melalui pembinaan peserta didik di SD Laboratorium UM Kota Blitar. Penelitian dilakukan secara kualitatif dengan pendekatan studi kasus. Data diperoleh melalui wawancara tidak terstruktur, observasi dan studi dokumentasi. Pengecekan kredibilitas data dilakukan dengan menggunakan teknik triangulasi, pengecekan anggota secara acak (random member check) dan diskusi teman sesama peneliti. Hasil penelitian ini menunjukkan strategi pembinaan peserta didik dalam rangka penguatan pendidikan karakter berbasis nilai pancasila dibagi ke dalam aspek pembelajaran dan non pembelajaran. Strategi penguatan pendidikan karakter berbasis nilai pancasila di sekolah dilaksanakan sesuai dengan visi dan misi sekolah termasuk disesuaikan dengan ciri khas pembelajaran sekolah yang berkiblat pada pola pendidikan barat dengan berfokus pada pemahaman dan penggunaan Bahasa Inggris sebagai keunggulan sekolah. Dipadukan dengan adat ketimuran yang dijabarkan dalam kegiatan pembinaan karakter peserta didik.Kata Kunci: strategi; penguatan pendidikan karakter; berbasis pancasila; sekolah laboratorium.